Investigating Pest Birds Problems and Potential Solutions in Sawah Ring, Tangkak - Razalee, Maizatul Leeqa; Norazlimi, Nor Atiqah (Journal of Sustainable Natural Resources, 2023)
In the agricultural sector, especially paddy fields, birds are considered pests when they destroy the paddy plants by eating the grains and reducing crop production. Pest birds are a common problem in agriculture. Nevertheless, studies of the pest birds, particularly on their distribution, ecology, and management, are still scarce in Malaysia. One of the significant pest birds in this case study is the Purple Swamphen (Porphyrio porphyrio). The objectives of this study are (1) to identify pest birds species (2) to investigate the behaviour of Purple Swamphen (Porphyrio porphyrio) and (3) to provide potential solutions for pest birds problems to local farmers at Sawah Ring, Tangkak. The methods used were direct observation using binoculars, spotter scope, and a digital camera. Besides that, a survey through the distribution of questionnaires and interviews was also conducted among the local people at the study site. Five species of pest birds have been recorded, which are, Purple Swamphen (Porphyrio porphyrio), Lesser Whistling Duck (Dendrocygna javanica), Scaly-breasted Munia (Lonchura punctulata), Javan Munia (Lonchura leucogastroides) and Baya Weaver (Ploceus philippinus). From the list, Purple Swamphen (Porphyrio porphyrio), was identified as the most disturbing pest bird. The occurrence of this species were marked at Block 1, Block 3, Block 15, Block 16, Block 18, and Block 19 at Sawah Ring, Tangkak, and the species’ behaviour (resting, nesting, feeding, etc.) was also recorded. In terms of solutions, several methods have been identified to overcome the pest bird problem based on the literature studies, such as physical and chemical repellent, buzzer and mesh networks, and also acoustic tools. Overall, pest birds are a significant problem in the paddy field areas of Sawah Ring, Tangkak. It reduced the quantity and quality of paddy production and caused losses to farmers. Understanding the occurrence and behaviour of pest birds is indeed crucial for better management of these pest bird species.